2013
DOI: 10.1371/journal.pone.0057882
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of miR-106b Promotes Cell Migration and Metastasis in Hepatocellular Carcinoma by Activating Epithelial-Mesenchymal Transition Process

Abstract: Hepatocellular carcinoma (HCC) is one the the most fatal cancers worldwide. The poor prognosis of HCC is mainly due to the developement of distance metastasis. To investigate the mechanism of metastasis in HCC, an orthotopic HCC metastasis animal model was established. Two sets of primary liver tumor cell lines and corresponding lung metastasis cell lines were generated. In vitro functional analysis demonstrated that the metastatic cell line had higher invasion and migration ability when compared with the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 28 publications
3
68
0
Order By: Relevance
“…Upregulation of microRNA-1290 impaired cytokinesis and affected the reprogramming of colon cancer cells (16). Overexpression of miR-106b promoted metastasis of hepatocellular carcinoma and correlated with higher tumor grade (17). In the present study miR-106b and miR-1290 had a significantly higher expression in tumor with compared to without lymphatic metastasis, suggesting that interference of the two miRNAs might depress the lymphatic metastasis of supraglottic LSCC.…”
Section: Discussionsupporting
confidence: 46%
“…Upregulation of microRNA-1290 impaired cytokinesis and affected the reprogramming of colon cancer cells (16). Overexpression of miR-106b promoted metastasis of hepatocellular carcinoma and correlated with higher tumor grade (17). In the present study miR-106b and miR-1290 had a significantly higher expression in tumor with compared to without lymphatic metastasis, suggesting that interference of the two miRNAs might depress the lymphatic metastasis of supraglottic LSCC.…”
Section: Discussionsupporting
confidence: 46%
“…Their study provided the evidence that miR-106b might serve as a causative agent in the malignant progression of pediatric BSG, thereby serving as a novel target for constraining the rapid and fatal course of pediatric BSG (Wang et al, 2012). Additionally, the study by Yau et al (2013) demonstrated that miR-106b was overexpressed in HCC tissues as compared with adjacent non-tumor tissue (P = 0.0005), and overexpression of miR-106b was significantly correlated with a higher tumor grade (P = 0.018). Further functional studies demonstrated that miR-106b could promote cell migration and stress fiber formation by overexpressing the RhoGTPases, RhoA and RhoC.…”
Section: Discussionmentioning
confidence: 97%
“…Further functional studies demonstrated that miR-106b could promote cell migration and stress fiber formation by overexpressing the RhoGTPases, RhoA and RhoC. In vivo functional studies also showed that overexpression of miR-106b promoted HCC metastasis (Yau et al, 2013). Moreover, Slaby et al (2010) found that miRNA-106b was significantly overexpressed in renal cell carcinoma (RCC) tissues (P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…27 Recently, miR-106b was also known to regulate EMT by the TGF-b/Smad signaling pathway implicated in cancer stem-like cell development. 25,28,29 The newly found target gene of miR-106b is Smad7, which acts as an inhibitor of TGF-b/Smad signaling. Smad7 binds to TGF-b receptor I and interrupts recruitment of TGF-b receptors I and II.…”
Section: Expression Of Cancer Stem Cell Markers and Spherementioning
confidence: 99%